Birth weight and adult bone mass: a systematic literature review. - Schlüssel, M; Vaz, J; Kac, G (2010)
SUMMARY: This systematic literature review comprised 16 studies. The association of birth weight with bone parameters was much more evident for bone mineral content (BMC) rather than bone mineral density (BMD). This is an important finding since a reduction in BMC is strongly associated with an increased risk of fractures. INTRODUCTION: The purpose of this study was to conduct a systematic literature review of studies that have investigated the association between birth weight (BW) and adult bone mass. METHODS: The search included English language articles, indexed in MEDLINE, using the key words: ("birth size" OR "birth weight" OR birthweight) AND (osteoporosis OR "bone mass" OR "bone density" OR "bone mineral density" OR "bone mineral content" OR "bone area"). A methodological quality appraisal of the reviewed studies was performed. RESULTS: Sixteen articles were reviewed. Eleven of 13 studies that measured BMC verified a positive effect of BW on this parameter, and nine even after adjustment for adult body size. Among the ten studies that found an unadjusted association between BW and BMD, two reported that the significance remained after adjustment for current body size. Interaction between prenatal and postnatal variables on the determination of adult bone mass was only tested by two studies. The results must be interpreted with caution due to the existence of few papers on the issue, as well as heterogeneous sample characteristics, investigated bone sites, and implemented analysis procedures. The aspects of methodological quality that frequently fail are as follows: representativeness of the planned and actually measured sample as well as proper adjustment for confounding. CONCLUSION: Based on the amount of accumulated evidence, it is probable that BW have a positive association with adult BMC rather than BMD, which is an important finding for clinical and public health policies since a reduction in BMC is strongly associated with an increased fracture risk.